SKRINING FITOKIMIA DAN BIOAKTIVITAS EKSTRAK DAN ISOLAT DARI DAUN TERAP (Artocarpus odoratissimus Blanco) - Erwin - (PROSIDING SEMINAR KIMIA, 2014)
steroid (isolate 1) and flavonoid (isolate 2) types have been isolated from n-hexane and chloroform fractions of Terap (Artocarpus odoratissimus Blanco) leaves, respectively. The types of compounds were determined by phytochemical test. Basic on the result of toxicity test against Brine shrimp lethality test (BSLT) shown that isolate 1 exhib ited highest toxic act ivity among others with LC 50 48.39 ppm.